Antidiabetic and Antioxidant Activities of 70% Ethanol-Diluted Extract of Piper Crocatum Leaves in Stretozotocin Induced Diabetic Rats - Jusup, Sinu Andhi (Fakultas Kedokteran Universitas Brawijaya, 2016)
Red betel plant (Piper crocatum) has been empirically used to cure diabetes mellitus. However, data regarding this plant are still limited. The aim of this study was to find antidiabetic and antioxidant activities of 70% ethanol-diluted extract of Piper crocatum leaves. Thirty Wistar rats aged 4 months were divided into 6 groups (I-VI) randomly. The groups of I-IV were injected with 40 mg i.p streptozotosin to induce DM. All groups were treated for 21 days. Group I (normal control group) and group II (diabetic control group) were given normal saline, while group III, IV, and V were treated with various doses of 70% ethanol-diluted extract of Piper crocatum Â leaves (50, 100, 200 mg/kg.b.w/day). Group VI (positive control group) was given glibenclamide 0,9 mg/kg.b.w/day. On day 21, the body weight, fasting blood glucose, plasma MDA, and insulin levels of all rats were examined. The data were processed using statistics to determine the effectiveness of antidiabetic and antioxidant activities of the extract. A significant decrease in fasting blood glucose and plasma MDA levels were observed in group III, IV, and V (p=0,00), when compared to group II (diabetic control group). A significant increase in body weight (p=0,04) and plasma insulin levels (p=0,008) occurred in group V only. In conclusion, seventy percent ethanol-diluted extract of Piper crocatum leaves has potential antidiabetic and antioxidant activities.